Trauma [a novel] - McGrath, Patrick 1950- (Knopf, 2008)
Growing up in a severely dysfunctional family, Charlie Weir builds a career as a psychiatrist in New York City, but the suicide of a patient, the breakup of his marriage, and a volatile other woman lead Charlie to question everything, even his own sanity.
Keywords: Psychologie; Psychiatrists -- Fiction; Adult children of dysfunctional families -- Fiction; Death -- Psychological aspects -- Fiction; New York (N.Y.) -- Fiction; Psychological fiction